The Influence of Hospital Image and Trust on Inpatient Satisfaction at Hospital X - Aziz, Abdul; Mulyana, Nana; Nuraini, Novia (IJBLE Scientific Publications Community Inc., 2025)
Low patient satisfaction can negatively impact hospital development, as dissatisfied patients may seek treatment elsewhere. Non-compliance with medical and nursing procedures is also common among dissatisfied patients. This study examines the influence of hospital image and trust on inpatient satisfaction at Hospital X using a quantitative approach with a cross-sectional design. The dependent variable, inpatient satisfaction, is measured through overall satisfaction, expectation, and experience, while the independent variables include hospital image (location, services, reputation) and trust (competence, benevolence, integrity).Findings indicate that hospital image significantly affects inpatient satisfaction (p = 0.006; OR = 5.293), and patient trust has an even stronger influence (p = 0.001; OR = 6.975). The R-Square value of 0.813 suggests that hospital image and trust explain 81.3% of satisfaction variance. Enhancing patient trust should be a strategic priority to improve inpatient satisfaction at Hospital X.